Achtsamkeit in der entwicklungsorientierten Suchtprävention und -therapie: Rational, Design und Ziele des Forschungsverbundes IMAC-Mind - Arnaud, Nicolas; Banaschewski, Tobias; Nees, Frauke; Bucholz, Verena Nadine; Klein, Michael; Reis, Olaf; Legenbauer, Tanja; Zapf, Antonia; Thomasius, Rainer (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2020)
Mindfulness in Development-oriented Approaches to Substance Use Prevention and Therapy: Rationale, Design and Objectives of the Research Consortium IMAC-Mind Substance use disorders (SUD) are a major contributor to morbidity and mortality. They are typically initiated during adolescence and can have fatal implications for healthy development. Despite substantial scientific advances, there remains a need to prioritize research directed at reducing risks for SUD, particularly in vulnerable periods and populations from a developmental perspective. Research indicates that reward sensitivity, impulsivity, deficient self-regulation, and stress reactivity develop markedly in childhood and adolescence and play an important role in the initiation and maintenance of SUD. A growing number of research results suggest that these factors can be favorably influenced by mindfulness-based interventions and that mindfulness-based exercises can be successfully integrated into established prevention and treatment programs. In this paper we summarize the conceptual relationships between the development and maintenance of addiction disorders and mindfulness, discuss existing empirical findings with regard to childhood and adolescence, and present the aims, study designs and intervention models of the subprojects from the ongoing research network "IMAC-Mind: Improving Mental Health and Reducing Addiction in Childhood and Adolescence through Mindfulness: Mechanisms, Prevention and Treatment".
CRIS-Team Scopus Importer:2020-07-17
Keywords: Achtsamkeit; children and adolescents; Entwicklungspsychopathologie; Kinder- und Jugendpsychiatrie; mindfulness; prevention; Selbstregulation; self-regulation; Substance Use Disorder; Substanzbezogene Störungen; therapy